Retrospective Comparison of Efficacy and Safety of Basiliximab and Antithymocyte Globulin in Kidney Transplant Recipients (Khartoum Journal of Pharmaceutical Sciences, 2021)
Background: Induction therapy with biological agents as anti-thymocyte globulin (ATG) or an interleukin 2 receptor antagonist (IL2-RA) is essential to reduce the risk of acute rejection.Though ATG is used selectively in patients with high immunological risk, the decision for induction treatment stays a matter of discussion in a patient with high immunological risk.Objective: To compare the efficacy and safety of Basiliximab versus Antithymocyte Globulin (ATG) in kidney transplant recipients (KTRs).Methodology:A retrospective study was conducted at Ahmed Gasim Hospital, Cardiac Surgery and Renal Transplantation center. Data was collected from all renal transplant recipients with intermediate immunological risk from January 2017 to August 2018. Data included the patient's demographics, efficacy, and frequency of adverse effects.Results: Out of 75 patients, 44 (58.7%) patients were treated with ATG, and 31(41.3%) with Basiliximab. Patient survival at one year was 97.7 % in the ATG treated group and 100 % in the Basiliximab treated group.While graft survival was similar in both groups (100%), and there was no delayed graft function in both groups, the incidence of acute rejection was 6.8 % and 6.5 % in the ATG and the Basiliximab treated group respectively. Infections were more prevalent in the ATG treated group 22.7% compared to 9.7% in Basiliximab treated group. Moreover, the rate ofhematological disorders was significantly higher in ATG treated group (61.4%) in comparison to Basiliximab treated group (29%)Conclusion: Both,ATG and Basiliximab induction therapy decreased acute rejection rates and they were associated with excellent one-year graft and patient survival rates. Basiliximab was effective as ATG in intermediate immunological risk patients with lower infections and hematological disorders rates and lower mortality rates.
Keywords: Anti-thymocyte globulin; Basiliximab; kidney transplant recipients